Inflation differentials of Euro countries and their determinants - Liargovas Panagiotis; Arvanitis Argyrios (Economies, 2023)
The purpose of this paper is to examine the inflation differentials and their determinants in the first twelve euro countries that formed the eurozone. We focus on only these countries to capture the effects through the last 22 years from 1999 to 2020, without taking into consideration the changes in dynamics that were caused due to the integration of more countries since 2007. The dynamic panel data results, estimated with the system Generalised Method of Moments estimation method, show that it is mostly structural and cyclical factors that drive inflation differentials among these euro countries and that there are no significant indications that other convergence processes have taken place during this time span to explain increase in certain countries' inflation. We conclude by mentioning the potential role that inflation differentials could play in the European Central Bank's decision-making process.
Keywords: 330; inflation differentials; inflation determinants; generalised method of moments; euro area